Effectiveness of Laser Acupoints on Women With Polycystic Ovarian Syndrome: A Randomized Controlled Trial - Elshamy, Fayiz F.; El-kholy, Sand; Abd El-Rahman, Marwa (Journal of Lasers in Medical Sciences, 2018)
Introduction: Polycystic Ovary Syndrome(PCOS), one of the most common causes of infertility. The aim of this study was to investigate the impact of laser acupuncture on PCOS women. Methods: Twenty-five PCOS women were randomly assigned to either the study group (SG; n= 13), which treated by laser acupuncture, or the control group (CG; n= 12). Blood hormonal levels and insulin resistance at baseline and after 12 weeks of intervention were measured. Results: The pre intervention showed no statistically significant differences between SG and CG for baseline characteristics ( p> 0.05). After 12 week intervention, Within group analyses showed that BMI, blood hormonal levels and insulin resistance were significantly decreased (p< 0.05), with no significant change in FSH (p> 0.05) in the two groups. Between group analyses showed that all outcomes measures were significantly decreased (p< 0.05) in SG compared to CG, with no significant changes in FSH and BMI(p> 0.05). Conclusion: Laser acupuncture can be suggested as an effective management for women with polycystic ovarian syndrome.